SOCIETAL JUDGEMENTS OF PHYSICAL APPEARANCE IN RELATION TO FOOD BEHAVIOUR, PHYSICAL ACTIVITIES, SMOKING AND INTERNET USE IN ADOLESCENTS SEEN IN THE PAEDIATRIC OBESITY AND DIABETES CLINIC - Affendi, Balqis Nur Sabrina; Ali, Hakima Muhamad; Zanalabidin, Nur Aimi Nabilah; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION The prevalence of childhood obesity and diabetes among adolescents in Malaysia is a concern. It affects the quality of life, and exposes to societal judgements related to physical appearance, which affects mental well-being. This study seeks to contribute valuable insights into the experiences of adolescents with obesity and diabetes and their implications for physical and mental health. METHODOLOGY Patients aged 12 to 18 years old attending the obesity and diabetes clinic at UMMC were invited to participate. A questionnaire-based assessment was offered. The questionnaire was adapted with consent from the NHMS 2017 committee. The study was approved by UMMC ethics. We analysed 4 components which include food behaviour, physical activities, smoking and internet usage. RESULT A total of 43 patients responded to the questionnaire. Forty-four percent (n=19) were males with 7.0% (n=3) recruited from the obesity clinic and 93.0% (n=40) from the diabetes clinic. Their mean age was 14.8 years old. Twelve (28%) reported that they were unhappy with their physical appearance. Amongst them, 79% (n=24) considered weight to be a very important aspect of their life. Eighteen (42%) reported consuming fruits less than once/day, while 20.9% (n=9) reported the same for vegetables. Additionally, 30% (n=15) did not drink milk at least once/day, while 4.6% (n=2) admitted to consuming carbonated drinks more than once/day. Eleven (25.6%) confessed to indulging in fast food more than twice/week. One respondent reported using e-cigarettes/vape more than three days/month and started vaping at the age of 14 years old. No one currently smokes. Seventeen (39.5%) reported infrequent physical activities less than once/week, while 52% (n=22) were driven to school. The majority 93% (n=40) were dependent on electronics, including smartphones, computers, and iPads, in their daily activities. CONCLUSION We anticipate that children with obesity and diabetes will encounter challenges with their mental and physical well-being. Understanding and addressing their daily behaviours and risk associated with lifestyle may be useful to prevent potential physical and mental health concerns.